Mesenteric Ischemia - Audu, Christopher O.; Schechtman, David W.; Davis, Frank M. (Clinics in Colon and Rectal Surgery, 2023)
Mesenteric ischemia occurs when perfusion of the visceral organs fails to meet normal metabolic requirements and subsequently results in abdominal symptoms such as diffuse postprandial pain, peritonitis, food fear, and weight loss. While generally divided into acute and chronic manifestations, mesenteric ischemia is commonly misdiagnosed at initial presentation due to the significant overlap with symptoms of other abdominal pathologies. Prompt recognition and diagnosis, mesenteric revascularization, and critical care management remain the mainstay of treatment in these patients for optimal outcomes. This review will highlight acute versus chronic mesenteric ischemia, their etiology, diagnostic criteria, treatment options, and will emphasize the joint role of the gastrointestinal and vascular surgeon in the timely management of this condition to prevent devastating outcomes.
Keywords: mesenteric ischemia; superior mesenteric artery; embolus; arrhythmia